A Ks-band-selected catalogue of objects in the ALHAMBRA survey. Issue 4 (23rd September 2016) - Nieves-Seoane, L.; Fernandez-Soto, A.; Arnalte-Mur, P.; Molino, A.; Stefanon, M.; Ferreras, I.; Ascaso, B.; Ballesteros, F. J.; Cristóbal-Hornillos, D.; López-Sanjuán, C.; Hurtado-Gil, Ll.; Márquez, I.; et al.
Abstract : The original ALHAMBRA catalogue contained over 400 000 galaxies selected using a synthetic F 814 W image, to the magnitude limit AB( F 814 W ) ≈ 24.5. Given the photometric redshift depth of the ALHAMBRA multiband data (〈z〉 = 0.86) and the approximately I -band selection, there is a noticeable bias against red objects at moderate redshift. We avoid this bias by creating a new catalogue selected in the K s band. This newly obtained catalogue is certainly shallower in terms of apparent magnitude, but deeper in terms of redshift, with a significant population of red objects at z > 1. We select objects using the K s band images, which reach an approximate AB magnitude limit K s ≈ 22. We generate masks and derive completeness functions to characterize the sample. We have tested the quality of the photometry and photometric redshifts using both internal and external checks. Our final catalogue includes ≈95 000 sources down to K s ≈ 22, with a significant tail towards high redshift. We have checked that there is a large sample of objects with spectral energy distributions that correspond to that of massive, passively evolving galaxies at z > 1, reaching as far as z ≈ 2.5. We have tested the possibility of combining our data with deep infrared observations at longer wavelengths, particularly Spitzer IRAC data.